The effects of component‐specific treatment compliance in individually tailored internet‐based treatment. (22nd February 2019) - Kraepelien, Martin; Blom, Kerstin; Lindefors, Nils; Johansson, Robert; Kaldo, Viktor
Abstract: The objective of this study was to explore the effects of treatment compliance in a guided individually tailored internet‐based treatment (TAIL) in relation to depression and co‐morbid symptoms. Compliance with the homework in the different treatment components in TAIL, each aimed at a specific condition, was rated for 207 participants by independent assessors. Six subgroups ( n = 34–131) were constructed consisting of participants with co‐occurring symptoms of worry, panic, social anxiety, stress, insomnia, or pain. For each group, hierarchical regression was used to investigate whether the total sum of compliance points, Overall Compliance, predicted reductions in depression and in condition‐specific symptoms. Also, in each subgroup, it was tested whether working with specific treatment components, Specific Compliance, predicted reduction of the targeted symptoms. Overall Compliance predicted 15% of the reduction in depression symptoms. For participants with worry, panic, social anxiety, stress, or insomnia, Overall Compliance also predicted symptom reductions in that specific condition. Specific Compliance predicted reduction in the targeted symptoms for participants with social anxiety, stress, and insomnia. Specific Compliance with stress and insomnia components also predicted reductions in depression. Our results strengthen the importance of compliance in internet‐based treatments. Because compliance with stress and insomnia components was particularly important for broad symptom reductions, these conditions should not be ignored when treating patients with co‐morbid symptoms.